2012
DOI: 10.1016/j.ajpath.2012.01.045
|View full text |Cite
|
Sign up to set email alerts
|

p53 and Mitochondrial DNA

Abstract: The roles and actions of the tumor suppressor protein p53 have been extensively studied with regard to nuclear events, including transcription and DNA damage repair. However, the direct roles of p53 in mitochondrial DNA (mtDNA) replication and function are less well understood. Studies herein used a mitochondrial-targeted p53 (MTS-p53) to determine its effects on both mtDNA abundance and mitochondrial function. MTS-p53 decreased cellular proliferation and mtDNA abundance in HepG2 cells transfected with wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…This study exploited a novel p53 construct that overexpresses p53 that is targeted within the mitochondrial matrix (Koczor et al, 2012). This was accomplished because the construct capitalized on the addition of a mitochondrial targeting sequence on the N-terminal side of human p53 while simultaneously removing the region encoding amino acids 291–393 to eliminate intrinsic nuclear localization of native p53 polypeptide (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study exploited a novel p53 construct that overexpresses p53 that is targeted within the mitochondrial matrix (Koczor et al, 2012). This was accomplished because the construct capitalized on the addition of a mitochondrial targeting sequence on the N-terminal side of human p53 while simultaneously removing the region encoding amino acids 291–393 to eliminate intrinsic nuclear localization of native p53 polypeptide (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial matrix-targeted p53 was designed as previously described (Koczor et al, 2012). Briefly, site-directed mutagenesis (Stratagene/Agilent, Santa Clara, CA) was utilized to introduce BsiWI restriction sites around the nuclear localization sequence contained in the C-terminal portion of WT p53 (amino acids 291–393) of a commercially available WT p53 plasmid (Clontech, Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One recent study revealed that mitochondrial disulfide relay causes translocation of p53 into mitochondria to facilitate its function for repairing oxidative damage to mitochondrial DNA [29]. However, overexpression of p53 in mitochondria would lead to depleted mitochondrial DNA abundance and a reduction in oxidative stress [30]. Oncogenic RAS-induced mitochondrial dysfunction, which causes oncogene induced senescence, is dependent on either p53 or RB [31].…”
Section: Dna-repair Factors and Mitochondrial Functionsmentioning
confidence: 99%